The survey of occupational accidents in Yazd gas agency (2013) - Amir Hossein Khoshakhlagh; Gholam Hossein Halvani; Ali Dehghani; Vahid Barzagar; Fereydon Laal; Hamid Mohammadi (The Journal of Qazvin University of Medical Sciences, 2016)
Background: Existence of coordinated and professional safety system to prevent occurrence of accidents and potential hazards seem to be essential in installing networks of gas distribution projects. Objective: To survey work-related accidents and safety performance indices in project implementation unit of Yazd gas agency. Methods: This analytical study was conducted on 197 of workforce in Yazd gas agency in 2013 that were selected by census and they were male. Demographic and accident information were gathered using a self-made questionnaire and face- to- face interview, and required information obtained from dossier to determine the safety performance indicators. Safety performance indicators were calculated in separately of 13 types occupations in project implementation unit of gas agency and data were analyzed using T-test. Findings: The highest accident frequency and severity rate were related to digging occupation and then metal line welding. Consequences of accidents were cuts (%56.7) and soreness (%14.9). The causes of accidents were related to uselessness of personal protective equipment (%25.2) and lack of precision in the task (%19.3). The highest rate of accident was observed among the age group 20-29 years with work experience of 4-6 years. Conclusion: According to the findings of this study and the risk of gas processes, it seems to be necessary the implementation of integrated management systems and training of workers about safety rules to improve the safety culture and prevent accidents.